Ritual Madduppa Baca Pada Masyarakat Islam di Desa Bulutellue Kabupaten Sinjai - Abdul Rahman (CV. Multi Kreasi Media, 2024)
This research aims to elaborate in depth about the madduppa reading ritual held by the Islamic community in Bulutellue Village. This research uses qualitative research methods where data is collected through observation and interviews. The collected data was then analyzed using a literature review in the form of books and journals relevant to the research topic. The results of the research show that the madduppa reading ritual is carried out as a hope that people who have died will be safe in the grave. This ritual consists of three stages, namely takzih, recitation of the Koran, and madduppa reading itself. This ritual persists to this day because people still consider it to have a function, namely strengthening solidarity, strengthening identity, and achieving peace of mind.